Butt laser welding-brazing of AZ31Mg alloy to Cu coated Ti-6Al-4V with AZ92 Mg based filler. (September 2019) - Liu, Jinge; Tan, Caiwang; Wu, Laijun; Zhao, Xiaoye; Zhang, Zequn; Chen, Bo; Song, Xiaoguo; Feng, Jicai
Highlights: Join Mg and Cu-coated Ti using laser welding-brazing process. Influence of Cu coating thickness on welding quality and interfacial reaction was studied. A elements diffusion mechanism on Mg/Cu-coated Ti interface was clarified. Joint strength and fracture path and were associated with interfacial bonding and thickness. Abstract: Butt laser welding-brazing of Mg to Ti with Mg based filler was performed with the assistance of Cu coating. The thickness of Cu coating was varied in the study, to investigate its influence on microstructure and mechanical properties of the joint. Two main regions were distinguished along the Mg/Cu coated Ti interface. At the upper interface, the bonding mechanism evolved from mechanical bonding into a "Ti3 Al and AlCu2 Ti" metallurgical bonding, and into a "Ti3 Al + Ti2 Cu + AlCu2 Ti" metallurgical bonding as Cu coating thickness varied from 0 μm to 19.7 μm to 24.9 μm. At the lower interface, mechanical bonding changed into the IMC layer consisted of Ti3 Al, Ti2 Cu and AlCu2 Ti when Cu coating thickness reached 28.2 μm. The chemical potential calculated by the developed Toop model suggested that Cu played a role in promoting the mutual diffusion between Al and Ti. Ti tended to react with Al first compared with Cu suggesting Ti-Al compounds were produced easily at Mg/Ti interface. In the case of Cu coating thickness of 19.7 μm, the joint load reached a peak value of 3457 N, as high as 85.35% of that of Mg base metal. The fracture mode changed from interfacial failure to fusion zone failure when the coating thickness reached 19.7 μm.